2014
DOI: 10.1007/s11223-014-9549-3
|View full text |Cite
|
Sign up to set email alerts
|

Research on Cutting-Temperature Field and Distribution of Heat Rates Among a Workpiece, Cutter, and Chip for High-Speed Cutting Based on Analytical and Numerical Methods

Abstract: Âûñîêîñêîðîñòíîå ðåçàíèå øèðîêî èñïîëüçóåòñÿ â àâèàêîñìè÷åñêîé, àâòîìîáèëüíîé è äðóãèõ îòðàñëÿõ ïðîìûøëåííîñòè. Îäíàêî êîìïëåêñíûé ìåõàíèçì ïðîöåññà âûñîêîñêîðîñòíîãî ðåçàíèÿ åùå íåäîñòàòî÷íî èçó÷åí. Íà îñíîâå àíàëèçà òåïëîâîãî ðàâíîâåñèÿ ìåaeäó òåïëîâûäåëåíèåì è ïîòðåáëåíèåì ýíåðãèè ïðè âûñîêîñêîðîñòíîé îáðàáîòêå áåç ñìàçî÷íî-îõëàaeäàþùåé aeèäêîñòè ïðåäëîaeåíû ìîäåëè òåïëîâûõ èñòî÷íèêîâ è ïîëåé òåìïåðàòóð ðåçàíèÿ. Äëÿ àíàëèçà âëèÿíèÿ âûäåëåíèÿ è âûõîäà òåïëà ïðè îáðàáîòêå íà âûñîêèõ ñêîðîñòÿõ ðåçàíèÿ âûâåäåíû… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It has brought a profound technological revolution to machinery manufacturing and will continue to have a significant and far-reaching impact [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. High-speed machining technology, which is a product of this new technology, is widely used in some critical sectors, such as the automobile manufacturing industry, the aerospace industry, and the engineering equipment field [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has brought a profound technological revolution to machinery manufacturing and will continue to have a significant and far-reaching impact [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. High-speed machining technology, which is a product of this new technology, is widely used in some critical sectors, such as the automobile manufacturing industry, the aerospace industry, and the engineering equipment field [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In machining it, the cutting speed and accuracy and the processing efficiency are all low besides chip is hard to break and the tool wear is serious. The merit of high-sped cutting can provide a new approach for solving above problem [2][3][4][5][6][7][8][9]. .Therefore, in this paper the deformation mechanism and surface finish and wearing character of cermet cutter cuting high manganese steel are studied, and the models of surface quality to optimize cutting parameters are offered by means of test data and linear regression method, which can be used to forecast suface quality machined for given cutting parameters or to decide cutting parameters for the required quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, no comprehensive mechanism of high-speed cutting behavior has as yet been comprehended completely. Models of thermal sources and fields of cutting temperature have been proposed for the analysis of thermal equilibrium between heat generation and energy consumption at high-speed dry cutting (An et al, 2014). In the article by Denkena et al (2010), it was shown that the temperature in the shear zone decreases with a decrease in the chip thickness.…”
Section: Introductionmentioning
confidence: 99%